The role of resistin as a regulator of inflammation: Implications for various human pathologies - Filková, Mária; Haluzík, Martin; Gay, Steffen; Senolt, Ladislav (Clinical immunology (Orlando, Fla.), 2009)
Resistin was originally described as an adipocyte-secreted peptide that induced insulin resistance in rodents. Increasing evidence indicates its important regulatory roles in various biological processes, including several inflammatory diseases. Further studies have shown that resistin in humans, in contrast to its production by adipocytes in mice, is synthesized predominantly by mononuclear cells both within and outside adipose tissue. Possible roles for resistin in obesity-related subclinical inflammation, atherosclerosis and cardiovascular disease, non-alcoholic fatty liver disease, rheumatic diseases, malignant tumors, asthma, inflammatory bowel disease, and chronic kidney disease have already been demonstrated. In addition, resistin can modulate several molecular pathways involved in metabolic, inflammatory, and autoimmune diseases. In this review, current knowledge about the functions and pathophysiological implications of resistin in different human pathologies is summarized, although there is a significant lack of firm evidence regarding the specific role resistin plays in the "orchestra" of the numerous mediators of inflammation.
Keywords: zánět; Resistin; nádory; obezita; Animals; lidé; Inflammation; Neoplasms; resistin; Obesity; Humans; zvířata